(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2020)
A strong academic reaction followed UNESCO’s decision to consecrate, in 2009, the Oath of the Manden as a cultural and intangible heritage. To summarize, the academic world, and in particular the French one, tried to challenge the idea according to which this oath, which dates back to 1222, has in fact been the first text disciplining human rights, well before European ones. If this is recognized, in fact, Africa, that is already the cradle of humanity, would have to be considered also the cradle for human rights and freedoms, subtracting that primacy to Europe. This article will try to analyse the reasons of the protesters, in order to offer a critical reading.